Effect of bile acid supplementation on endogenous lipid synthesis in patients with short bowel syndrome: A pilot study. Issue 3 (March 2020) - Mouillot, Thomas; Beylot, Michel; Drai, Jocelyne; Hillon, Patrick; Gelas, Patrick; Lauverjat, Madeleine; Brondel, Laurent; Chambrier, Cécile
Summary: Background & aims: Short bowel syndrome patients (SBS) receiving parenteral nutrition (PN) often have dyslipidaemia and can develop intestinal failure-associated liver disease (IFALD). These patients demonstrate increased cholesterol synthesis and hepatic lipogenesis. These lipid disturbances may be due to a decreased concentration of the bile acid pool or malabsorption. The aim of this pilot study was to evaluate the effect of bile acid administration on lipid synthesis in patients with SBS. Methods: The 24 h fractional synthesis rate (FSR) of cholesterol and triglycerides was measured by the isotopic method (deuterated water) before and after 4 months of ursodeoxycholic acid (UDCA) treatment (20 mg/kg/day). Five short bowel patients (age: 53.4 ± 19.2 years) who had normal liver function and lipid plasmatic profiles received 1920 ± 300 ml of PN for 151 ± 74 days (mean PN energy intake was 27.0 ± 6.0 kcal/kg body weight, composed with 3.87 ± 1.38 g/kg of carbohydrate, 0.72 ± 0.25 g/kg of fat and 1.10 ± 0.23 g/kg of amino acids). Plasma metabolites, liver enzymes, 7-α-OH-cholesterol and steatosis levels were also evaluated before and after treatment. Student's t-tests were performed, and the results were expressed in means (±SD). Results: After treatment, decreases in the absolute values of cholesterol synthesis (0.31 ± 0.12 mmol L −1 to 0.24 ± 0.11 mmol L −1 ; p < 0.05), FSR of cholesterol (31.6 ± 4.7% to 26.4 ± 4.7%; p = 0.06) and FSR of triglycerides (12.8 ± 5.8% to 9.2 ± 5.5%; p < 0.01) were observed. Cholesterol and alanine aminotransferase concentrations also decreased (ALT) (p < 0.05). The absolute values of triglyceride synthesis and triglyceride concentrations remained unchanged. Conclusions: In SBS patients, UDCA decreases the hepatic synthesis of triglycerides and cholesterol. These results suggest that UDCA could prevent the onset of the IFALD. Highlights: Patients with SBS receiving PN have increased cholesterol synthesis and hepatic lipogenesis. A daily oral intake of UDCA (20 mg/kg/day) reduces the endogenous synthesis of both cholesterol and triglycerides. UDCA could improve lipid metabolism in patients with chronic intestinal failure and prevent cholestasis.